The story of civil rights - Mara, Wil (DK. Beginning to read alone., 2018)
A history of race relations in the U.S. includes coverage of slavery, abolition and segregation as well as the events of the Civil Rights movement, discussing subjects ranging from protests and speeches to legislation and the famous people around the world who helped promote equal rights.